Hemodynamic signal changes during volitional swallowing in dysphagia patients with different unilateral hemispheric stroke and brainstem stroke: A near-infrared spectroscopy study - Xiancong Ma; Yang Peng; Lida Zhong; Fang Li; Zhouquan Tang; Xiao Bao; Jingjun Chen (Brain Research Bulletin, 2024)
Background and objectives: Strokes will result in decreased in cortical excitability and changed in the balance between the affected and unaffected hemispheres. Previous studies have focused on cortical changes in healthy subjects during swallowing, while they remain unknown in patients with stroke at different locations. Thus, the purpose of this study was to research cortical activation patterns of swallowing in patients with dysphagia and healthy subjects by the functional near-infrared spectroscopy (fNIRS). We also focus on the comparability of brain activation areas associated with swallowing between patients with different stroke locations and healthy subjects. Methods: total of 104 participants were invited to our study, involving 86 patients with dysphagic unilateral hemispheric stroke and 18 age and sex matched healthy controls. The stroke patients were categorized into patients with left unilateral stroke lesions (n = 30), patients with right unilateral stroke lesions (n = 32) and patients with brainstem injury (n = 24) according to different stroke sites. All patients underwent a series of clinical swallowing function assessments, such as the Fiberoptic endoscopic dysphagia severity scale (FEDSS), penetration-aspiration scale (PAS) of Rosenbek, the gugging swallowing screen (GUSS) and the functional oral Intake scale (FOIS) after informed consent has been signed. All participants received the fNIRS system assessment. Results: The results showed that extensive areas of the cerebral cortex activated during the swallowing tasks in healthy participants (P < FDR 0.05). For patients with left unilateral stroke lesions, the HbO concentration were strongest over the right hemisphere (P < FDR 0.05). In addition, a less severe activation was also observed in the left hemisphere. Comparable to patients with left unilateral stroke lesions, the strongest activation during swallowing task were found in the left hemisphere in patients with right unilateral stroke lesions (P < FDR 0.05). Similarly, the right hemisphere also has activated less. In contrast, patients with brain stem injury showed more bilaterally activation patterns. Conclusion: Our finding states that cortical activation areas differ between patients with different stroke locations and healthy subjects during swallowing. There was a more bilateral activation in healthy participants and patients with lesions in the brainstem while more cortical activation in unaffected hemisphere in patients with unilateral hemispheric stroke. It also provides a basis for the future treatment of dysphagia after stroke.